Transgenic Rat Models of Huntington’s Disease - Carreira, J.C.; Jahanshahi, A.; Zeef, D.; Kocabicak, E.; Vlamings, R.; von Hörsten, S.; Temel, Y. (Springer Verlag service@springer.de, 2014)
Several animal models for Huntington’s disease (HD) have been created in order to investigate mechanisms of disease, and to evaluate the potency of novel therapies. Here, we describe the characteristics of the two transgenic rat models: transgenic rat model of HD (fragment model) and the Bacterial Artificial Chromosome HD model (full-length model). We discuss their genetic, behavioural, neuropathological and neurophysiological features. © Springer-Verlag Berlin Heidelberg 2013.
Keywords: BACHd; Basal Ganglia; Behaviour; Huntington’s Disease; Neuropathology; Neurophysiology; Striatum; Transgenic Rat Model